Eosinophilic gastroenteritis – a manifestation of an allergic disease in the gastrointestinal tract? Part 1. Epidemiology and diagnosis - Kuźmiński, Andrzej; Rosada, Tomasz; Przybyszewska, Justyna; Ukleja-Sokołowska, Natalia; Bartuzi, Zbigniew (Gastroenterology Review/Przegląd Gastroenterologiczny, 2023)
Eosinophilic gastroenteritis (EGE) is a relatively rare disease, but it should be considered whenever a patient presents with unexplained gastrointestinal symptoms that cannot be explained by parasitic infection or other gastrointestinal diseases characterized by eosinophilic infiltration. A high coexistence of EGE and allergic diseases has been documented. Diagnosis of EGE is based primarily on clinical, endoscopic, and histopathological findings. Glucocorticosteroids and other immunomodulatory drugs are the mainstay of treatment, but currently the greatest hope lies in biological drugs, which are undergoing intensive research. This disease is troublesome for the patient and significantly reduces the quality of life.